2021
DOI: 10.20473/fmi.v57i1.14661
|View full text |Cite
|
Sign up to set email alerts
|

Body Mass Index, Waist-Hip Ratio and Fasting Blood Glucose Levels amongst the University Students

Abstract: Overweight and obesity have been correlated to the higher risk for developing metabolic diseases in later life, i.e. DM type 2. We study the body mass index (BMI), the waist to hip ratio (WHR) and the fasting blood glucose levels (FBG) in the seemingly healthy male and female university students to comprehend these variables amongst the youth in Indonesia in 2019. The BMI and WHR of 150 male and female students aged 18-22 years old of the IIKBW, Kediri were measured by standardised anthropometry. The FBG was m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
1
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 21 publications
0
0
1
1
Order By: Relevance
“…This study reveals that the majority of students had a healthy BMI (64.21%) and that the proportion of students with overweight and obesity is the same (14.74%). The prevalence of overweight is approximately 18% and obesity is approximately 30.7%, which is quite low compared to previous studies conducted among university students in Indonesia [14]. Higher prevalence of obesity and overweight compared to this study also found in other countries like Boston (34% of females and 32% of males), India (27%), Qatar (46% of males and 44% of females), and Morocco (42%) [15][16][17][18].…”
Section: Discussioncontrasting
confidence: 71%
“…This study reveals that the majority of students had a healthy BMI (64.21%) and that the proportion of students with overweight and obesity is the same (14.74%). The prevalence of overweight is approximately 18% and obesity is approximately 30.7%, which is quite low compared to previous studies conducted among university students in Indonesia [14]. Higher prevalence of obesity and overweight compared to this study also found in other countries like Boston (34% of females and 32% of males), India (27%), Qatar (46% of males and 44% of females), and Morocco (42%) [15][16][17][18].…”
Section: Discussioncontrasting
confidence: 71%
“…Tingkat gula darah puasa yang lebih tinggi lebih sering terjadi pada wanita dibandingkan pria. 28 Penelitian yang telah ada lebih banyak meneliti hubungan indeks massa tubuh dengan kadar gula darah puasa. Penelitian ini menggunakan kadar gula darah sewaktu.…”
Section: Hubungan Indeks Massa Tubuh Dengan Kadar Gula Darahunclassified